Productivity and diversity of annually harvested reconstructed prairie communities. Issue 2 (29th September 2018) - Kordbacheh, Farnaz; Jarchow, Meghann; English, Lydia; Liebman, Matt
Abstract: Biofuel production from cellulosic feedstocks may increase during the next century. To be sustainable, this production should protect environmental quality and biodiversity. Fertilized mixed‐species prairie can deliver substantial quantities of cellulosic ethanol per unit land area with minimal losses of NO3 ‐N in drainage water, but the long‐term maintenance of biodiversity in such systems has been uncertain. We report how nitrogen, phosphorus, and potassium fertilizer application, precipitation, and time affected the species composition and productivity of reconstructed prairie communities harvested annually as biofuel feedstocks over a 9‐year period. Results indicated that both precipitation and fertilizer application drove above‐ground biomass production, with the greatest response to fertilizer occurring in wetter than average years. Fertilization reduced species richness, but increased species evenness. Consequently, Simpson's diversity index did not differ between the fertilized and unfertilized communities, though it declined in both communities over time. A total of 59 plant species was recorded, with eight of them explaining most of the differences in vegetation cover between the fertilized and unfertilized treatments. After 9 years, the high fertility community was dominated by the C4 grass Andropogon gerardii, the C3 grass Elymus canadensis, and the non‐leguminous forbs Heliopsis helianthoides, Helianthus maximiliani, and Monarda fistulosa, whereas the low fertility community was dominated by the C4 grasses A. gerardii and Sorghastrum nutans, the C3 grass E. canadensis, and the non‐leguminous forb M. fistulosa . Fertilization increased the abundance of flowering forbs available to pollinators in the early, middle and late portions of the growing season. Synthesis and applications . Results of our study suggest that maintenance of reasonably high levels of productivity and biodiversity are possible in fertilized prairie communities harvested annually for bioenergy, with plant cover more evenly distributed among different functional groups. In the future, if policy and markets favour biofuels and better delivery of ecosystem services from harvested land, prairie‐based feedstocks could become part of a renewable energy portfolio that fosters biodiversity and contributes to the provision of floral resources for pollinators. Abstract : Results of our study suggest that maintenance of reasonably high levels of productivity and biodiversity are possible in fertilized prairie communities harvested annually for bioenergy, with plant cover more evenly distributed among different functional groups. In the future, if policy and markets favour biofuels and better delivery of ecosystem services from harvested land, prairie‐based feedstocks could become part of a renewable energy portfolio that fosters biodiversity and contributes to the provision of floral resources for pollinators.